2017
DOI: 10.20360/g2mp4g
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers’ Perspectives on the Use of Multicultural Literature in Their Classrooms

Abstract: This qualitative study set out to determine how multicultural literature was used and perceived by US elementary school teachers, and how the beliefs of teachers shape perceptions, selection, interpretation, and the teaching of multicultural literature (Ketter & Lewis, 2001).Twenty-six (26) elementary school teachers across the country responded to this study. An invitational email with a web-survey hyperlink was utilized. Variables pertaining to participant background, definition, selection acquirement and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Rudine Sims Bishop (1990) posits that authentic and rich representation of diverse protagonists and stories in young adult and children’s literature is a powerful catalyst for students to discover various cultures and their values, which behaviors are acceptable and appropriate, and how one must function to be a contributing member of society. When students whose identities are sidelined see themselves in texts used in the classroom, they understand that their perspectives and lived experiences are both important and valued by other members of the learning community and society (Holland, Mongillo, & Paterson, 2016; Lopez-Robertson & Haney, 2017). The incorporation of diverse texts and curricula also creates opportunities for students to explore experiences and perspectives that are different from their own.…”
Section: Calls To Action For Educatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rudine Sims Bishop (1990) posits that authentic and rich representation of diverse protagonists and stories in young adult and children’s literature is a powerful catalyst for students to discover various cultures and their values, which behaviors are acceptable and appropriate, and how one must function to be a contributing member of society. When students whose identities are sidelined see themselves in texts used in the classroom, they understand that their perspectives and lived experiences are both important and valued by other members of the learning community and society (Holland, Mongillo, & Paterson, 2016; Lopez-Robertson & Haney, 2017). The incorporation of diverse texts and curricula also creates opportunities for students to explore experiences and perspectives that are different from their own.…”
Section: Calls To Action For Educatorsmentioning
confidence: 99%
“…The incorporation of diverse texts and curricula also creates opportunities for students to explore experiences and perspectives that are different from their own. This humanizing knowledge and appreciation for others can combat prejudice and bias while promoting acceptance and empathy (Holland, Mongillo, & Paterson, 2016). By actively exploring literature and curricula by and about people of diverse identities, students learn to embrace their own identities while developing empathy and inclusion for those who do not share those identities.…”
Section: Calls To Action For Educatorsmentioning
confidence: 99%
“…The education system should teach citizens to live in diversity because with a multicultural education system can teach cognitive abilities and competitive values to individuals to be able to blend with a diverse society [10]. Multicultural must be integrated into the education curriculum by giving teachers an understanding that multicultural education is important to be understood by students when the learning process in the class, so that it can foster positive behavior in the social environment [11]. Multicultural education facilitates quality interaction between individuals who present various ideas and perspectives to choose the right steps in solving problems in diverse social lives [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rather than monitoring for fidelity of implementation, administrators can meet with teachers, individually or in grade-level teams, to develop and sustain their pedagogical understandings and decision-making about how to create and find openings in their day to bring in diverse texts and hold read-alouds.Provide Support for Primary Teachers' Read-Alouds With DiverseChildren's Literature. In their study,Holland and Mongillo (2016) found that elementary teachers were more likely to share multicultural literature when they had the backing of their administrators. Primary teachers, especially novice teachers, then, will require ongoing support and professional development in their work with DCL.…”
mentioning
confidence: 96%